Identity practices of English teachers in Brazilian digital communities - de Jesus, Dánie Marcelo (Revista Leitura, 2019)
This study investigates the identity practices of three virtual communities directed to English teachers – “English Language Teachers”, “English Teachers in Brazil”, and “I am an English Teacher” – in order to understand how teachers’ professional identities are constructed in the discourse of community members. The study is grounded on Critical Discourse Analysis (Fairclough, 2000). The research methodology is interpretive and the analysis seeks identity representations that materialise in users’ linguistic choices. Findings reveal an attempt to set a traditional professional identity for foreign language teachers in their respective communities. DOI: 10.28998/2317-9945.2014v1n53p81-103